THE EFFECT OF GOOD CORPORATE GOVERNANCE ON CORPORATE ZAKAT WITH PROFITABILITY AS AN INTERVENING VARIABLE (EMPIRICAL STUDY ON ISLAMIC COMMERCIAL BANKS IN INDONESIA FOR THE 2020-2024 PERIOD) - Farida Ulfa; Rizky Fadhillah (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2025)
This study aims to examine the effect of Good Corporate Governance on corporate zakat with profitability as an intervening variable at Islamic Commercial Banks in Indonesia during the period 2020-2024. This study uses a quantitative approach with the path analysis method processed using WarpPLS 6.0 software. The sample was selected through purposive sampling method of three banks that consistently reported their corporate zakat. The results showed that Good Corporate Governance has a significant negative effect on profitability, but has no significant effect on corporate zakat. On the other hand, profitability has a significant positive effect on corporate zakat. In addition, Good Corporate Governance is also proven to have an indirect effect on corporate zakat through profitability as a mediating variable. These findings indicate that the implementation of good corporate governance must be supported by improved financial performance so that social obligations such as zakat can be realized optimally.